Laser processing of engineering materials : principles, procedure and industrial application - Ion, John C. (Elsevier/Butterworth-Heinemann, 2005)
The complete guide to understanding and using lasers in material processing!Lasers are now an integral part of modern society, providing extraordinary opportunities for innovation in an ever-widening range of material processing and manufacturing applications. The study of laser material processing is a core element of many materials and manufacturing courses at undergraduate and postgraduate level. As a consequence, there is now a vast amount of research on the theory and application of lasers to be absorbed by students, industrial researchers, practising engineers and production managers. Wr.